2016
DOI: 10.9778/cmajo.20160021
|View full text |Cite
|
Sign up to set email alerts
|

Early mobilization of critically ill adults: a survey of knowledge, perceptions and practices of Canadian physicians and physiotherapists

Abstract: Physicians and physiotherapists in the ICU underestimated the incidence of ICU-acquired weakness and felt inadequately trained to mobilize patients receiving mechanical ventilation. We identified multiple modifiable barriers to early mobilization at the institutional, health care provider and patient levels that need to be addressed when designing mobilization programs for critically ill adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
76
1
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 28 publications
13
76
1
14
Order By: Relevance
“…Most of the nurses reported that they have not gone through patient early mobilization training which was consistent with the results reported by Koo et al [35]. It was doubtful whether non-mobilization trained nurses able to provide optimum care for patient early mobilization.…”
Section: Discussionsupporting
confidence: 82%
“…Most of the nurses reported that they have not gone through patient early mobilization training which was consistent with the results reported by Koo et al [35]. It was doubtful whether non-mobilization trained nurses able to provide optimum care for patient early mobilization.…”
Section: Discussionsupporting
confidence: 82%
“…The barriers to EM most frequently cited by physicians were the unavailability of professionals on the team and of sufficient time to routinely mobilize patients, excessive sedation and delirium. ( 15 , 17 ) Risk of musculoskeletal self-injury and excessive stress at work were also mentioned by nurses and physical therapists as barriers to EM.…”
Section: Discussionmentioning
confidence: 99%
“…These barriers were also reported by members of multi-professional teams in the United States ( 15 ) and Canada. ( 17 ) Time and the professionals required to mobilize critically ill patients might be considerable hindrances to EM in the ICU. In addition, they represent a frequently reported concern in regard to the improvement of the quality of care needed to facilitate the acceptance of mobilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is the approach of early mobilization in critically ill adults (20). In a survey in academic ICUs in Canada (20) both physicians and physiotherapists underestimated the incidence of ICUAW and felt inadequately trained to mobilize patients receiving mechanical ventilation.…”
Section: Exclusion Criteriamentioning
confidence: 99%